The drone's eye: applications and implications for landscape architecture. (3rd October 2018) - Kullmann, Karl
Abstract: The use of next-generation automated consumer drones for aerial imaging and mapping is increasingly common. As a field that recurrently seeks new mapping methods, the practical aspects of drone imaging and mapping are most evidently applicable to landscape architecture. However, as a social art, landscape architecture also has a vested interest in the cultural implications of the consumer-oriented features of next-generation drones. This article bridges these professional and amateur domains of drone use. First, the article uses a topographically complex case study site to compare drone functionality against established imaging and mapping technologies. Second, the article interprets the potential implications of these applications on the practice and theory of landscape architecture. The article concludes that high fidelity drone mapping has the capacity to refocus contemporary landscape discourse from a predominantly satellite-based viewpoint to the site scale at which landscape is both experienced and designed.